Scanning the Effects of Ethyl Methanesulfonate on the Whole Genome of Lotus japonicus Using Second-Generation Sequencing Analysis. Issue 4 (1st April 2015) - Mohd-Yusoff, Nur Fatihah; Ruperao, Pradeep; Tomoyoshi, Nurain Emylia; Edwards, David; Gresshoff, Peter M; Biswas, Bandana; Batley, Jacqueline
Abstract: Genetic structure can be altered by chemical mutagenesis, which is a common method applied in molecular biology and genetics. Second-generation sequencing provides a platform to reveal base alterations occurring in the whole genome due to mutagenesis. A model legume, Lotus japonicus ecotype Miyakojima, was chemically mutated with alkylating ethyl methanesulfonate (EMS) for the scanning of DNA lesions throughout the genome. Using second-generation sequencing, two individually mutated third-generation progeny (M3, named AM and AS) were sequenced and analyzed to identify single nucleotide polymorphisms and reveal the effects of EMS on nucleotide sequences in these mutant genomes. Single-nucleotide polymorphisms were found in every 208 kb (AS) and 202 kb (AM) with a bias mutation of G/C-to-A/T changes at low percentage. Most mutations were intergenic. The mutation spectrum of the genomes was comparable in their individual chromosomes; however, each mutated genome has unique alterations, which are useful to identify causal mutations for their phenotypic changes. The data obtained demonstrate that whole genomic sequencing is applicable as a high-throughput tool to investigate genomic changes due to mutagenesis. The identification of these single-point mutations will facilitate the identification of phenotypically causative mutations in EMS-mutated germplasm.